Panacea for the nanoplastic surge in Africa: A state-of-the-art review. Issue 11 (November 2022) - Okeke, Emmanuel Sunday; Ejeromedoghene, Onome; Addey, Charles Izuma; Atakpa, Edidiong Okokon; Bello, Semiu Folaniyi; Ezeorba, Timothy Prince Chidike; Chukwudozie, Kingsley Ikechukwu; Okoye, Charles Obinwanne
Abstract: Africa is a large continent ranked amongst the top consumer of plastic materials. However, the improper handling of plastic wastes has resulted in massive pollution of different aspects of the environment (water, soil, sediments, air, food, etc.) within and around the region. The fragmentation and biodegradation of the bulk plastic material into small-sized particles has given rise to microplastic and nanoplastics. Owing to their small sizes, ease of transport, and large surface area, they tend to wreak serious havoc in the environment. Nevertheless, the growing awareness of the pollution problems caused by micro/nanoplastic debris is instrumental towards circumventing its widespread across the ecosystem. This review provides a state-of-the-art information on the prevailing nanoplastic surge across the borders of Africa, the ineffective management policies of plastic wastes, potential environmental hazards, and possible remediation strategies. Additionally, prospective insights into new areas for advanced research were highlighted. Graphical abstract: Image 1 Highlights: The paradigm shift from MPs to NPs has been elucidated. The production, consumption, and waste generation of NPs in Africa have been discussed. The impacts, detection, and remediation strategies for NPs have been exhaustively reviewed. Problems facing the management of NPs pollution in Africa have been carefully explained. Future prospects on NPs management in Africa have been suggested. Abstract : Microplastics; Nanoplastics; Environmental hazards; Plastics; Paradigm shifts; Africa.